Performance of Electrical Power Distribution Network Under Dynamic Loading - Ramadoni Syahputra; Taufiq Akbar; Faaris Mujaahid (Universitas Muhammadiyah Yogyakarta, 2018)
This paper presents the performance of the electrical power distribution network under dynamic loading. The performance of a distribution system can be seen from the power losses generated by the network. If the power losses are low, then it can be said that network performance is excellent. Another parameter is the distribution network voltage profile. The voltage profile is significant in the distribution network. A very long distribution line will cause a voltage drop at the end of the network. This condition is very undesirable, so efforts must be made to improve the distribution network voltage profile. The method for correcting the voltage profile is by installing capacitors or reconfiguring the network. In this study, an evaluation of the performance of the distribution network at PLN Temanggung was conducted. The results showed that several network points experienced below-standard voltage drops. Therefore it is recommended to install power capacitors or reconfigure the networks.